2007
DOI: 10.1152/jn.01178.2006
|View full text |Cite
|
Sign up to set email alerts
|

Combined Voltage and Calcium Epifluorescence Imaging In Vitro and In Vivo Reveals Subthreshold and Suprathreshold Dynamics of Mouse Barrel Cortex

Abstract: Cortical dynamics can be imaged at high spatiotemporal resolution with voltage-sensitive dyes (VSDs) and calcium-sensitive dyes (CaSDs). We combined these two imaging techniques using epifluorescence optics together with whole cell recordings to measure the spatiotemporal dynamics of activity in the mouse somatosensory barrel cortex in vitro and in the supragranular layers in vivo. The two optical signals reported distinct aspects of cortical function. VSD fluorescence varied linearly with membrane potential a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

9
172
0

Year Published

2008
2008
2022
2022

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 166 publications
(182 citation statements)
references
References 57 publications
9
172
0
Order By: Relevance
“…We showed previously in brain slices that bolus loading of L5 (either in vivo or in vitro) filled the dendrites of L5 specifically and sufficiently to give dendritic signals while the nearby neuropil in the upper layers gave no signal (15). In the same experiments, we found that EPSPs had a negligible effect on intracellular Ca 2ϩ as have others (21)(22)(23). We examined the effect of back-propagating action potentials (BPAPs) on dendritic Ca 2ϩ by applying TTX to block Na ϩ channels first to the cortical surface and then injected to L5.…”
Section: Discussionsupporting
confidence: 58%
“…We showed previously in brain slices that bolus loading of L5 (either in vivo or in vitro) filled the dendrites of L5 specifically and sufficiently to give dendritic signals while the nearby neuropil in the upper layers gave no signal (15). In the same experiments, we found that EPSPs had a negligible effect on intracellular Ca 2ϩ as have others (21)(22)(23). We examined the effect of back-propagating action potentials (BPAPs) on dendritic Ca 2ϩ by applying TTX to block Na ϩ channels first to the cortical surface and then injected to L5.…”
Section: Discussionsupporting
confidence: 58%
“…These findings suggest that resting-state BOLD activity may thus reflect synaptic input and local cortical processing rather than neuronal output. VSD activity can indicate both super-and sub-threshold voltage activity but tends to correlate best with sub-threshold membrane potential changes 61 . As such, VSD imaging as performed in this study may be particularly apt at investigating infraslow fluctuations that may underlie similar processes related to spontaneous BOLD signal fluctuations.…”
Section: Discussionmentioning
confidence: 99%
“…Fluorescent signals derived from VSD imaging in vivo are composed primarily of postsynaptic membrane potentials from neurons located in superficial cortical layers (Ferezou et al, 2006;Berger et al, 2007). Using this approach, we show that 3-7 d of whisker disuse in fully mature mice leads to synaptic depression in multiple cortical regions associated with processing sensory information from the deprived whisker.…”
Section: Mechanisms Of Experience-based Cortical Depressionmentioning
confidence: 98%